SPRi-Based Biosensing Platforms for Detection of Specific DNA Sequences Using Thiolate and Dithiocarbamate Assemblies - Drozd, Marcin; Pietrzak, Mariusz D.; Malinowska, Elżbieta (Frontiers in Chemistry, 2018)
The framework of presented study covers the development and examination of the analytical performance of surface plasmon resonance-based (SPR) DNA biosensors dedicated for a detection of model target oligonucleotide sequence. For this aim, various strategies of immobilization of DNA probes on gold transducers were tested. Besides the typical approaches: chemisorption of thiolated ssDNA (DNA-thiol) and physisorption of non-functionalized oligonucleotides, relatively new method based on chemisorption of dithiocarbamate-functionalized ssDNA (DNA-DTC) was applied for the first time for preparation of DNA-based SPR biosensor. The special emphasis was put on the correlation between the method of DNA immobilization and the composition of obtained receptor layer. The carried out studies focused on the examination of the capability of developed receptors layers to interact with both target DNA and DNA-functionalized AuNPs. It was found, that the detection limit of target DNA sequence (27 nb length) depends on the strategy of probe immobilization and backfilling method, and in the best case it amounted to 0,66 nM. Moreover, the application of ssDNA-functionalized gold nanoparticles (AuNPs) as plasmonic labels for secondary enhancement of SPR response is presented. The influence of spatial organization and surface density of a receptor layer on the ability to interact with DNA-functionalized AuNPs is discussed. Due to the best compatibility of receptors immobilized via DTC chemisorption: 1.47 ± 0.4 ·1012 molecules ∙ cm-2 (with the calculated area occupied by single nanoparticle label of ~132.7 nm2), DNA chemisorption based on DTCs is pointed as especially promising for DNA biosensors utilizing indirect detection in competitive assays.